The antimicrobial and antibiofilm potential of sweet basil essential oil on Streptococcus mutans and Staphylococcus aureus - Nurhayati Mohamad Zain,; Nabilah Mohd Amin,; Fatin Athirahusna Nordin,; Junaidah Mahmud,; Indah Mohd Amin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The antimicrobial and antibiofilm activities of sweet basil essential oil (SBEO) against oral microorganisms, Streptococcus mutans (S. mutans) and Staphylococcus aureus (S. aureus) were determined in this study. The antimicrobial activities were evaluated using the disk diffusion method (DDM), where Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were tested against both bacteria. Different formulations of SBEO (microemulsion, emulsion, water) were tested for biofilm dispersion assay on 24 h of preformed biofilm. Commercial chlorhexidine (CHX) 0.12% w/v was used as a positive control. The scanning electron microscope (SEM) was used to observe the changes on the treated surface. The data were analyzed using SPSS Version 27.0. A Kruskal-Wallis test followed by a Post-hoc Mann-Whitney U test was applied, and the level of significance was set at p<0.05. All formulations of SBEO showed antimicrobial activities against the tested microorganisms. Exposure to 2.5% (v/v) microemulsion for two min exhibited 42.56% and 32.10% (p<0.001) of biofilm dispersion for S. mutans and S. aureus, respectively. The SEM micrographs revealed the number of microorganisms on the treated group surface reduced compared to the negative controls. SBEO exerts an antimicrobial and antibiofilm effect on S. mutans and S. aureus. This finding suggests that the SBEO microemulsion has the potential to control planktonic S. mutans and S. aureus and their biofilm formation in the oral environment.